2010
DOI: 10.1186/1471-2172-11-60
|View full text |Cite
|
Sign up to set email alerts
|

In vivo trafficking and immunostimulatory potential of an intranasally-administered primary dendritic cell-based vaccine

Abstract: BackgroundCoccidioidomycosis or Valley fever is caused by a highly virulent fungal pathogen: Coccidioides posadasii or immitis. Vaccine development against Coccidioides is of contemporary interest because a large number of relapses and clinical failures are reported with antifungal agents. An efficient Th1 response engenders protection. Thus, we have focused on developing a dendritic cell (DC)-based vaccine for coccidioidomycosis. In this study, we investigated the immunostimulatory characteristics of an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Earlier studies have reported that EP67 engaged the C5aR on the surface of human DC and facilitated presentation of T and B cell epitopes to which EP67 was conjugated [12,16]. Denditric cells have been suggested to be major contributors to the host protective response to Coccidioides infection by bridging between the innate and adaptive immune systems [43]. …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported that EP67 engaged the C5aR on the surface of human DC and facilitated presentation of T and B cell epitopes to which EP67 was conjugated [12,16]. Denditric cells have been suggested to be major contributors to the host protective response to Coccidioides infection by bridging between the innate and adaptive immune systems [43]. …”
Section: Discussionmentioning
confidence: 99%
“…The DCs were cotransfected with Coccidioides -Ag2/PRA-cDNA and a plasmid DNA encoding HSV1-TK. HSV1-TK phosphorylates 18 F-FIAU to phospho- 18 F-FIAU, which is then metabolically trapped and detected by the PET system (Vilekar et al 2010). As noted by this study, 111 In-oxine SPECT imaging for DC trafficking does not ensure the integrity of radiolabel and DC association in vivo, has poor resolution, and lastly allows imaging only up to 3 or 4 days.…”
Section: Potential In Vivo Imaging Tools To Study DC Trafficking Intomentioning
confidence: 99%
“…We used immortalized C57BL/6 mouse-derived JAWS II dendritic cells that show typical immunophenotype and morphology when cultured in presence of GM-CSF. The characteristics of these immortalized cells have been described in our previous reports [ 14 , 24 ].…”
Section: Resultsmentioning
confidence: 96%